A study of spiritual leadership values in a Malaysian education institution - Wong, Shiet Ching *; Malissa Maria Mahmud, *; Fatimah Omar, (2012)
The study is to explore the set of spiritual leadership values embraced by Malays, Chinese and Indians leaders or managers in a Malaysian educational institution. Spiritual leadership values enable employee to work intrinsically for an organization. This is a qualitative study which utilized semi structured interview. The study revealed understanding and praise are the common values, however, there are some differing values which were discovered among the three races. The study provides an understanding of spiritual leadership values which upheld by the three races in Malaysia.